# Find the sum of the first 15 terms of an AP whose fifth and ninth terms are 26 and 42 respectively.

Answer

Verified

382.5k+ views

Hint: Consider any AP whose first term is a and the common difference is d. Use the formula that the \[{{n}^{th}}\] term of AP can be written as \[{{a}_{n}}=a+\left( n-1 \right)d\] and the sum of n terms of an AP is \[{{S}_{n}}=\dfrac{n}{2}[2a+\left( n-1 \right)d]\]. Write equations based on the data given in the question and solve them to find the sum of first 15 terms of AP.

Complete step-by-step answer:

We have to find the sum of the first 15 terms of an AP whose fifth term is 26 and ninth term is 42.

We will assume that the first term of an AP is given by a and the common difference is given by d. We will now write any general term of an AP.

So, we can write the\[{{n}^{th}}\] term of AP as \[{{a}_{n}}=a+\left( n-1 \right)d\].

Substituting \[n=5\] in the above equation, we have \[{{a}_{5}}=a+\left( 5-1 \right)d=26\].

Simplifying the above equation, we have \[a+4d=26.....\left( 1 \right)\].

Substituting \[n=9\] in the above formula, we have \[{{a}_{9}}=a+\left( 9-1 \right)d=42\].

Simplifying the above equation, we have \[a+8d=42.....\left( 2 \right)\].

We will now solve equation (1) and (2). Subtracting equation (1) from equation (2), we have \[a+8d-\left( a+4d \right)=42-26\].

Thus, we have \[4d=16\].

\[\Rightarrow d=4\]

So, the value of common difference d is \[d=4\].

Substituting the value \[d=4\] in equation (1), we have \[a+4\left( 4 \right)=26\].

Thus, we have \[a=26-16=10\].

Thus, the first term of AP is \[a=10\].

We will now evaluate the sum of the first 15 terms of AP.

We know that the sum of first n terms of AP is given by \[{{S}_{n}}=\dfrac{n}{2}[2a+\left( n-1 \right)d]\].

Substituting \[n=15,a=10,d=4\] in the above equation, we have \[{{S}_{15}}=\dfrac{15}{2}[2\left( 10 \right)+\left( 15-1 \right)4]\].

Simplifying the above expression, we have \[{{S}_{15}}=570\].

Hence, the sum of the first 15 terms of an AP whose fifth and ninth terms are 26 and 42 respectively is given by 570.

Note: Arithmetic Progression is a sequence of numbers such that the difference between any two consecutive terms is a constant. To find the sum of the first 15 terms, we can find all the 15 terms and then add them to get their sum. However, it will be very time consuming. So, it’s better to use the formula of finding sum of n terms to AP.

Complete step-by-step answer:

We have to find the sum of the first 15 terms of an AP whose fifth term is 26 and ninth term is 42.

We will assume that the first term of an AP is given by a and the common difference is given by d. We will now write any general term of an AP.

So, we can write the\[{{n}^{th}}\] term of AP as \[{{a}_{n}}=a+\left( n-1 \right)d\].

Substituting \[n=5\] in the above equation, we have \[{{a}_{5}}=a+\left( 5-1 \right)d=26\].

Simplifying the above equation, we have \[a+4d=26.....\left( 1 \right)\].

Substituting \[n=9\] in the above formula, we have \[{{a}_{9}}=a+\left( 9-1 \right)d=42\].

Simplifying the above equation, we have \[a+8d=42.....\left( 2 \right)\].

We will now solve equation (1) and (2). Subtracting equation (1) from equation (2), we have \[a+8d-\left( a+4d \right)=42-26\].

Thus, we have \[4d=16\].

\[\Rightarrow d=4\]

So, the value of common difference d is \[d=4\].

Substituting the value \[d=4\] in equation (1), we have \[a+4\left( 4 \right)=26\].

Thus, we have \[a=26-16=10\].

Thus, the first term of AP is \[a=10\].

We will now evaluate the sum of the first 15 terms of AP.

We know that the sum of first n terms of AP is given by \[{{S}_{n}}=\dfrac{n}{2}[2a+\left( n-1 \right)d]\].

Substituting \[n=15,a=10,d=4\] in the above equation, we have \[{{S}_{15}}=\dfrac{15}{2}[2\left( 10 \right)+\left( 15-1 \right)4]\].

Simplifying the above expression, we have \[{{S}_{15}}=570\].

Hence, the sum of the first 15 terms of an AP whose fifth and ninth terms are 26 and 42 respectively is given by 570.

Note: Arithmetic Progression is a sequence of numbers such that the difference between any two consecutive terms is a constant. To find the sum of the first 15 terms, we can find all the 15 terms and then add them to get their sum. However, it will be very time consuming. So, it’s better to use the formula of finding sum of n terms to AP.

Recently Updated Pages

Which of the following would not be a valid reason class 11 biology CBSE

What is meant by monosporic development of female class 11 biology CBSE

Draw labelled diagram of the following i Gram seed class 11 biology CBSE

Explain with the suitable examples the different types class 11 biology CBSE

How is pinnately compound leaf different from palmately class 11 biology CBSE

Match the following Column I Column I A Chlamydomonas class 11 biology CBSE

Trending doubts

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Draw a diagram of a plant cell and label at least eight class 11 biology CBSE

What is 1 divided by 0 class 8 maths CBSE

How would you explain the phase diagram of sulfur class 11 chemistry CBSE

State the laws of reflection of light

Draw a diagram of nephron and explain its structur class 11 biology CBSE

One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE

What is the z value for a 90 95 and 99 percent confidence class 11 maths CBSE

How fast is 60 miles per hour in kilometres per ho class 10 maths CBSE